Managerial Competency Transformation as the Key to Strategic Decision-Making in the Era of Dynamic Education - Herdiana Herdiana; Nurlaila Nurlaila (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Significant changes in the world of education and the world of work due to globalization, advances in science and technology, and social dynamics require education leaders to have adaptive and strategic managerial competencies. Managerial competencies are no longer limited to technical administrative skills, but also include critical thinking skills, effective communication, visionary leadership, data-based decision making, and the ability to adapt to change. The world of education is currently in a phase of transition, marked by policy changes, curriculum development, the penetration of digital technology in the learning process, and demands for improved quality of education amid limited resources. These conditions require quick and accurate strategic decision-making from education leaders, ranging from school or madrasah principals to education institution managers and policy makers and decision makers. However, weak managerial capacity remains a major obstacle to responding effectively to change, resulting in slow transformation of educational institutions. The transformation of managerial competencies, particularly in the aspects of visionary leadership, human resource management, technology utilization, and strategic decision-making, is a major focus for the sustainability and competitiveness of educational institutions. This study uses a descriptive qualitative approach with library research methods to explore the concepts and practices of transforming managerial competencies in the world of education.